Fiber-matrix adhesion in glass fiber reinforced thermoplastic composite laminates and its effect on mechanical properties - Moritzer, Elmar; Brandes, Philipp; Wittler, Maurice; Claes, Leander; Wippermann, Mareen; Haag, Markus; Gries, Thomas; Henning, Bernd (International Polymer Processing)
With the growing demand for lightweight solutions to reduce emissions, especially in the transportation, automotive and aerospace sectors, recyclable, continuous fiber-reinforced plastic composite laminates with a thermoplastic matrix are of rising interest. To achieve their maximum mechanical properties, the fiber-matrix adhesion (FMA) is critical. In this work, continuous fiber-reinforced thermoplastic laminates (CFRTPL) with a polypropylene (PP) matrix and twill woven glass fiber fabrics are produced by film stacking. The films used contain different amounts of maleic-anhydride-grafted PP (MA-g-PP) as a coupling agent to produce CFRTPL of different mechanical strengths. To analyze the FMA, the CFRTPL are subjected to Charpy-impact and tensile tests. Additionally, single fiber pull-out tests (SFPT) are conducted to further investigate the effect of MA-g-PP on the FMA. The results of the SFPT show an improvement in apparent interfacial shear strength (AIFSS) when the MA-g-PP content is increased, which can be attributed to an increase in FMA. However, the research shows that MA-g-PP has a low impact on the mechanical properties if the force is applied parallel to the warp and weft threads during tensile testing and the results of the Charpy-impact testing suffer from embrittlement of the matrix material. Subsequently, the results of this study are compared to three-point flexural tests conducted in a previous study. It can be concluded that tensile and impact tests are not suited to investigate FMA on a macroscopic scale, while SFPT and flexural tests provide a better alternative.

Assessing solids conveying in injection moulding machines using coupled numerical simulations based on the discrete element method (DEM) and multibody systems (MBS) - Landgräber, Jan; Schöppner, Volker; Brüning, Florian (International Polymer Processing)
Abstract Design of single screw machines for polymer processing often focuses on the melt dominated areas of the screw. However, solids conveying is a key aspect for processes with high screw speeds, grooved feed sections, small screw diameters and material with low bulk density. In injection moulding, throughput limitations are highly relevant in packaging applications as due to low cooling times, plasticizing affects the cycle time. In addition, insufficient solids conveying is a primary cause for air residues in the melt and final product. Therefore, well-designed feed sections are required, especially as direct processing of regrind in recycling applications becomes more relevant due to governmental restrictions. Existing models for injection moulding are based on analytical equations and do not allow to assess new feed sections and feed opening designs, adapted to high screw speeds or regrind. In this paper, numerical simulations based on the Discrete Element Method (DEM), previously used in the field of extrusion, are carried out. In order to replicate the cyclic, superimposed rotation and translation of the screw, a coupled approach of DEM and Multibody Systems Simulation (MBS) is pursued. To verify the accuracy of such coupled simulations, a special test setup is added to a conventional injection moulding machine. Pure solids conveying is investigated, as DEM does not accommodate for large plastic deformations or melting. Different screw and intake designs as well as smooth and grooved barrels are investigated. Selected resins, pellet shapes and regrind are processed, varying the processing parameters and comparing the results to the simulation. The coupled approach replicates reality well in terms of throughput, confirming that DEM can be utilised to further investigate process phenomena and develop calculation models for solids conveying in injection moulding.

Modeling of Solid Conveying Pressure Throughput Behavior of Single Screw Smooth Barrel Extruders under Consideration of Backpressure and High Screw Speeds - Schöppner, Volker; Trippe, J. (International Polymer Processing)

Numerical Analysis and Evaluation of Process and Geometry Specific Transient Temperature Fields for a New Variation of Gas-Assisted Injection Molding - Moritzer, Elmar; Seidel, S. (International Polymer Processing)

Experimental Investigation of PC-Films Using Optical Measurements - Dammann, C.; Caylak, Ismail; Mahnken, Rolf (International Polymer Processing)
Abstract The alignment of polymer chains is a well known microstructural evolution effect due to straining of polymers. This has a drastic influence on the macroscopic properties of the initially isotropic material. In this work, cold forming is performed at room temperature on a tensile testing machine. Polycarbonate films are examined in two loading phases. In the first phase, the specimen is loaded to induce anisotropy, and in the second, it is re-loaded, while the material direction is varied. The investigations are supported by an optical measurement system to gain knowledge about the inhomogeneous material behavior in the initial loading phase and about the anisotropic homogeneous behavior during the re-loading phase. Two dimensional strain contours are obtained from the test data. Additionally, we propose a method for approximation of the macroscopic true stress and compare the results with a common approach based on volume consistency. In the future, the test data will set a basis for parameter identification of constitutive equations taking into account a combination of inhomogenous and homogenous material behavior, exhibiting strain induced anisotropy.